Long-term survival outcomes of Wagner™ conical stems in crowe non-IV hip dysplasia: a retrospective analysis - D’Angelo, Fabio; Pautasso, Andrea; Antognazza, Delia; Monestier, Luca; Gervasini, Mattia; Filipponi, Marco; Bernardi, Chiara; Riva, Giacomo (Frontiers in Surgery, 2025)
BackgroundTotal hip arthroplasty (THA) is one of the most frequently performed orthopedic procedures. Developmental dysplasia of the hip (DDH) presents specific anatomical challenges that require tailored implant designs. Wagner™ conical stems were developed to address the morphological alterations of dysplastic femur, offering potential advantages in stability and functional restoration. This study assesses the long-term survival and clinical outcomes of Wagner™ conical stems in patients with Crowe non-IV DDH.Materials and methodsThis retrospective study included primary THAs performed between 2003 and 2015 using Wagner™ conical stems exclusively in patients with DDH. Only cases with complete clinical and radiographic follow-up were analyzed, excluding those lost to follow-up or revised. The evaluated outcomes were prosthetic survival rate, clinical performance assessed with the Modified Harris Hip Score (mHHS), and radiographic findings at final follow-up.ResultsForty-five patients (57 hips) met the inclusion criteria. The mean age at surgery was 56.5 years (range, 33–76), with a mean follow-up of 15 years (range, 8–20). Kaplan–Meier analysis showed a survival rate of 95.7% at 10 years and approximately 80.5% at 20 years, with an overall survival rate of 89.5% at the final follow-up. The main cause of failure was aseptic loosening, followed by infection, recurrent dislocation, and metallosis. Among hips with retained implants, 86.3% (44/51) achieved an mHHS > 70, indicating satisfactory functional recovery. The mean mHHS was 88.6 ± 14.3 (Range, 62–100), with a median of 92 and a mode of 100.ConclusionWagner™ conical stems provide durable fixation and favorable long-term functional outcomes in Crowe non-IV DDH, with high survival rates and low complication incidence over extended follow-up.